Preclinical and clinical studies for transplant tolerance via the mixed chimerism approach - Sasaki, Hajime (Hum Immunol, 2017)
Based upon observations in murine models, we have developed protocols to induce renal allograft tolerance by combined kidney and bone marrow transplantation (CKBMT) in non-human primates (NHP) and in humans. Induction of persistent mixed chimerism has proved to be extremely difficult in major histocompatibility complex (MHC)-mismatched primates, with detectable chimerism typically disappearing within 30–60 days. Nevertheless, in MHC mismatched NHP, long-term immunosuppression-free renal allograft survival has been achieved reproducibly, using a non-myeloablative conditioning approach that has also been successfully extended to human kidney transplant recipients. CKBMT has also been applied to the patients with end stage renal disease with hematologic malignancies. Renal allograft tolerance and long-term remission of myeloma have been achieved by transient mixed or persistent full chimerism. This review summarizes the current status of pre-clinical and clinical studies for renal and non-renal allograft tolerance induction by CKBMT. Improving the consistency of tolerance induction with less morbidity, extending this approach to deceased donor transplantation and inducing tolerance of non-renal transplants, are critical next steps for bringing this strategy to a wider range of clinical applications.